2017
DOI: 10.1007/s00170-017-1310-1
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and strengthening mechanisms in an Al-Mg-Si alloy processed by equal channel angular pressing (ECAP)

Abstract: The microstructure, mechanical properties, and strengthening mechanisms of an Al-Mg-Si alloy (AA6060) subjected to severe plastic deformation using equal channel angular pressing (ECAP) were investigated. Samples were passed through a die with an inner angle of F = 90° and outer arc of curvature of ¿ = 37° at room temperature up to 12 passes via route Bc. Electron backscatter diffraction (EBSD) was used to evaluate the microstructure and misorientation boundaries. The microstructure showed a large fraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 55 publications
2
30
1
Order By: Relevance
“…Therefore, the possibility of increasing the amount of deformation that can be accumulated by increasing the pre-annealing temperature and time promotes the formation of new grains and reduces the number of subgrains. The misorientation distribution of boundaries obtained from the EBSD data and displayed in Figure 6c,d correspond to a bimodal type with two clear different populations-low and high angles-as usually reported in the literature for highly deformed samples [15][16][17][18][19][20]. Present results are also in agreement with Chang et al's observations [21].…”
Section: Characterization Of the Microstructure At Maximum Number Passessupporting
confidence: 91%
“…Therefore, the possibility of increasing the amount of deformation that can be accumulated by increasing the pre-annealing temperature and time promotes the formation of new grains and reduces the number of subgrains. The misorientation distribution of boundaries obtained from the EBSD data and displayed in Figure 6c,d correspond to a bimodal type with two clear different populations-low and high angles-as usually reported in the literature for highly deformed samples [15][16][17][18][19][20]. Present results are also in agreement with Chang et al's observations [21].…”
Section: Characterization Of the Microstructure At Maximum Number Passessupporting
confidence: 91%
“…However, the observed strength improvement, which was lower than that with the ECAP method [23,24], was achieved at the expense of ductility, which decreased from 30.1% to about 13.2% after the first DRECE pass; then with an increase in strain accumulation, it decreased to 8.4% after the six DRECE passes. Such changes in strength and ductility are typical for severely deformed metals, as proved in numerous research papers [4,16,25,26].…”
Section: Evolution Of Microstructurementioning
confidence: 67%
“…a decrease in the grain size with ECAP and a smaller average grain size for ECAP-RH samples. Indeed, as stated in the literature, grain refinement during ECAP was commonly linked to the formation of HAGBs due to recrystallisation processes [15,28,45]. To confirm these restùts and avoid the problems due to the identification of grains, the total length of boundaries was calculated for each sample (Fig.…”
Section: Grain Size = 24 µMmentioning
confidence: 99%
“…Al-Mg Si alloys [ 4,[12][13][14]. Khelfa et al observed a 97 % decrease in the grain size after only one ECAP pass in AA 6060 T6 [15]. Sitdikov et al showed the evolution of the texture during ECAP processing in Al-Mg Sc alloy [16].…”
Section: Introductionmentioning
confidence: 99%